Benthic diatoms and some environmental conditions in three lowland streams - Licursi, Magdalena (2002)
This article reports on the ecological preferences of benthic diatoms in relation to pH, conductivity and organic pollution-eutrophication and their tolerance spectrums. Three Pampean streams subjected to different human impacts were studied. The bottom substrate of these streams is mostly composed of slime-clay with low proportions of gravel and sand; in consequence, the epipelon is the most represented benthic community. Samples were taken seasonally between 1997-1998 at 9 sampling sites. In each sampling station ten sub-samples were collected by pipetting a superficial layer (5-10 mm) of sediment from different places. Physico-chemical parameters were measured. Considering the ranges of pH, conductivity and organic pollution-eutrophication the diatom's tolerance spectrums were established. 162 diatom species were identified. More than 50 % of species occurred in sites where the conductivity was lower than 600 μS cm-1. More than 50 % of species had their preference range in sites with moderate organic matter and nutrient content. Diatom species found show defined preferences for organic pollution-eutrophication, but show less consistent responses for conductivity and, particularly, hydrogen ions content.